Want More? Learn Less: Motivation Affects Adolescents Learning from Negative Feedback - Zhuang, Yun; Feng, Wenfeng; Liao, Yu (Frontiers in Psychology, 2017)
The primary goal of the present study was to investigate how positive and negative feedback may differently facilitate learning throughout development. In addition, the role of motivation as a modulating factor was examined. Participants (children, adolescents and adults) completed two forms of the guess and application task (GAT). Feedback from the Cool-GAT task has low motivational salience because there are no consequences, while feedback from the Hot-GAT task has high motivational salience as it pertains to receiving a reward. The results indicated that negative feedback leads to a reduction in learning compared to positive feedback. The effect of negative feedback was greater in adolescent participants compared to children and adults in the Hot-GAT task, suggesting an interaction between age and motivation level on learning. Further analysis indicated that greater risk was associated with a greater reduction in learning from negative feedback and again, the reduction was greatest in adolescents. In summary, the current study supports the idea that learning from positive feedback and negative feedback differs throughout development. In a rule-based learning task, when associative learning is primarily in practice, participants learned less from negative feedback. This reduction is amplified during adolescence when task-elicited motivation is high.